ARca: PENGEMBANGAN BUKU INTERAKTIF BERBASIS AUGMENTED REALITY PADA PENGENALAN DAN PEMBELAJARAN CANDI PRAMBANAN DENGAN SMARTPHONE BERBASIS ANDROID - , Andria K. Wahyudi, Dr. Ridi Ferdiana, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lesson of history is part of the effort to preserve the culture and values of the nation. However, the learning process is often less attractive to be studied. This study proposes one solution to the interactive history learning named ARca. ARca is included combined software and the physical book as a medium of learning, which will bring the information of 3D models that represent the real objects Prambanan temple, audio, animation, and additional text as complementary information. This study emphasizes the process of developing a prototype as one of the case study to implement markerless-based techniques of augmented reality, implement the virtual button to interact with the system that had not been previously applied to books in the past, testing aplication with a variety of conditions, and applying ARca on the real learning situation. The result is a printed version and Android software that allows the interaction beween book and students, which is devoted as a learning medium that can display augmented reality 3D models of temples, information, and an explanation of the Prambanan temple. ARca can be run on a Entry-Level smartphone which is 1 Ghz Processor, 3.2 MP camera, OS Android 4.0.4 ICS, OpenGL ES 2.0 support, and 512 RAM so that it can be used in almost every type of smartphone. Based on the testing of the respondents obtained more than 75% expressed an interest in learning the history by using ARca. The 85% responder States that ARca really useful if applied to learning process, thus proving augmented reality can increase student interest in studying the Prambanan temple.